DIGITAL LEARNING USING BLENDED POE2WE MODEL IN ENGLISH LESSON FOR FACING 21ST CENTURY CHALLENGES - Sulastri Herdiani (Siliwangi University, 2020)
This study aims to (1) describe the steps of Blended POE2WE model in English lesson; (2) test the effectiveness of the Blended POE2WE model in English lesson, and (3)describe the attitudes and activities of teachers and students when implementing the Blended POE2WE model in English lesson at one of the senior high schools in Ciamis, Indonesia. The method used in this research is mixed method. Data collection techniques used in this study are questionnaire, observation and documentation. Likert scale is used to measure attitudes, opinions, and perceptions of teachers and students. To measure the effectiveness of the POE2WE blended model in English lesson, a t-test was used using SPSS software with the provision that t count t table. The results show that the steps of learning using Blended POE2WE models were in accordance with 21st century competence (4C). The t-test on the final test between the model and control groups in each class is as follows: (1) t-test on the final test of class X Social 2 with the X Social 5 is t = 13.189; (2) t-test on the final test of class X Social 3 with the X Social 5 is t = 14.946; (3) t-test on the final test of class X Social 4 with the X Social 5 is t = 6.290. Based on the data analysis results, it can be concluded that the final ability test for students in the control class has a significant difference (t tabel 1.66) so that this model is effective to use for improving student achievement in English lesson. Meanwhile, the students’ attitudes towards the implementation of the POE2WE blended model showed improvement, by which students' attitudes towards the learning process is 60.18%, towards the teaching materials is 54.63% and towards the English teachers is 71.29%.